Oliguric acute kidney injury as a main symptom of bradycardia and arteriosclerosis resolved by pacemaker implantation: a case report - Pliquett, Rainer U (BioMed Central, 2014)
INTRODUCTION: Cardiovascular comorbidities regularly determine renal function. We report a case of acute kidney injury (Acute Kidney Injury Network stage 3) due to an intermittent third-degree atrioventricular block, which had not been diagnosed before. CASE PRESENTATION: A 76-year-old Caucasian man with liver cirrhosis due to non-alcoholic fatty liver disease, and type-2 diabetes was cognitively impaired and had reduced vigilance presumably caused by hepatic encephalopathy and/or Alzheimer dementia. Within 2 years, two hospitalizations occurred for syncope attributed to orthostatic failure and hypovolemia. During the last hospitalization, oliguric acute kidney injury occurred. Sonography ruled out a post-renal cause. His renal resistive index was 1.0; his heart rate was below 50 beats per minute. After cessation of beta-blocker therapy, Holter electrocardiogram showed a new intermittent third-degree atrioventricular block with pauses for less than 3 seconds. Pacemaker insertion resolved his acute kidney injury, despite resumption of beta-blocker therapy. During four months of follow-up, syncope has not occurred, and vigilance was stable. However, his renal resistive index of 1.0 remained. CONCLUSIONS: Here, typical neurologic symptoms of bradycardia were misclassified. Diagnostic work-up of oliguric acute kidney injury revealed intermittent third-degree heart block. The pathomechanism of acute kidney injury relates to relevant bradycardia and increased vascular stiffness attenuating arterial diastolic renal blood flow.